Optimizing Health E-Leaflet Education Media to Increase Knowledge of Hypertension Patients at the Pancoran Community Health Center - Safira, Anggia Putri; Juliani, Enni; Panjaitan, Ribka Sabarina (Jurnal Keperawatan Profesional (KEPO), 2025)
Hypertension was a health problem frequently encountered in society and was known as a “silent killer” because it showed no symptoms but could lead to serious complications such as stroke, kidney failure, and heart disease. One important effort in controlling hypertension was increasing patient knowledge. However, health education delivered without attractive media was often less effective. This study aimed to determine the effect of optimizing health e-leaflet educational media on increasing the knowledge of hypertension patients at the Pancoran Community Health Center. The research method was quantitative with a quasi-experimental design using a pretest–posttest with a non-equivalent control group approach. A total of 116 subjects were involved and divided into two groups: an experimental group that received education using health e-leaflets and a control group that did not receive educational media. Data were collected using a questionnaire and analyzed univariately and bivariately using the Mann–Whitney U test. The results showed a significant difference in knowledge between the experimental and control groups with a p-value < 0,001. It was concluded that health e-leaflet educational media had a significant effect on increasing the knowledge of hypertension patients at the Pancoran Community Health Center. Health e-leaflet media could be used as an alternative approach for health education in the digital era.